Development of finger heart rate sensor monitor using Graphical User Interface (GUI) in MATLAB - Abdullah, Farah (2006)
The aim of this paper is to develop the finger heart rate sensor monitor system using Graphical User Interface (GUI) in MATLAB. The samples of normal pulse wave from the developed finger heart rate sensor monitor are loaded into the system where MATLAB mathematical software is used to perform the analysis to calculate and display the heart rate. The finger heart rate sensor monitor developed, outputs an analog signal that represent the cardiovascular pulse wave that is found throughout the human body. This pulse wave will result in a change in the volume of arterial blood with each pulse beat the heart rate is calculated based on the difference between the time occurrences of the peak amplitude of two consecutive pulses. In this paper, the performance of this monitoring system is tested by using the real data. An analog to digital converter (ADC) is also designed to interface the analog signal obtained from the hardware to the computer for real-time processing. However the ADC needs to be further improved for better output performance.